Analysis of migration of pathogenic drug-resistant bacteria to soils and groundwater after fertilization with sewage sludge. - Ewa Stańczyk-Mazanek; Longina Stępniak (PLoS ONE)
The paper discusses the analysis of the effect of using sewage sludge for fertilization on the level of soil and groundwater contamination with drug-resistant bacteria. Other sanitary contaminants in these environments were also analysed. Composted sewage sludge was introduced into the sandy soil over a period of 6 months. The examinations were conducted under conditions of a lysimetric experiment with the possibility of collecting soil leachates (in natural conditions). The following doses of sewage sludge were used: 0, 10, 20, 30 and 40 t/ha calculated per experimental object containing 10 kg of sandy soil. The research were carried out within the time frame of one year. Dactylis glomerata grass was grown on the fertilized soils. In soils and leachates from soils (which may have polluted groundwater) collected from fertilized experimental objects, the sanitary condition and quantity of drug-resistant bacteria (mainly from the families Enterobacteriaceae and Enterococcus) were analysed one year after fertilization. Their drug resistance to selected antibiotics was also analysed based on current recommendations. The study showed that fertilization with sewage sludge (even after stabilization and hygienization) results in contamination of soil and infiltrating waters with many species of drug-resistant pathogenic bacteria. The lowest level of contamination of soil and water environment was found after the application of sewage sludge at a dose of 10 t/ha. The isolated drug-resistant strains of intestinal bacteria were less sensitive to older generations of antibiotics including cefazolin, ampicillin, and co-amoxiclav.